BANKING ACTIVITY IN THE FERGHANA VALLEY: EMERGENCE AND ITS PREREQUISITES IN THE XIX—XX CENTURIES (Scientific journal of the Fergana State University, 2024)
The aim of this paper is to analyse in detail the banking activities in the Ferghana Valley in the period from the 19th to the 20th century with a focus on identifying the factors that contributed to the emergence of the banking system in this region. The research methodology includes analysis of historical documents, statistical data and literary sources in order to reconstruct the context of banking sphere formation in the Fergana Valley. The results of the study make it possible to reveal the stages of formation and development of banking activity in the region, as well as to identify the main reasons for its emergence. The influence of the banking system on the economic structure and social processes in the Ferghana Valley is considered in the context of the general dynamics of the region's development. The findings of the study emphasise the importance of the banking sector in shaping the economic landscape of the Ferghana Valley and its impact on various aspects of social life. The work provides a basis for a deeper understanding of the role of banking in the historical development of the region and has potential implications for the current economic strategy of the area.